PEMANFAATAN MEDIA SOSIAL INSTAGRAM @EDUKASIPARLEMEN DALAM MENINGKATKAN CITRA - Fairuz, Fara Dilla; Hanifah, Ummy; Ningsih, Titiek Surya (CAKRAWALA: JURNAL HUMANIORA BINA SARANA INFORMATIKA, 2024)
The mass media always reports negative information about the DPR RI, it has an impact on a negative image of the DPR RI institution and political parties. Based on the LSI survey for the period March 31-April 4 2023, the level of public trust of DPR RI institution and political parties only gained 5%. Therefore the Secretariat General of the DPR RI utilizes social media Instagram as a media for promotion, dissemination and public education through the account @edukasiparlemen. The research method used in this research is qualitative, descriptive in nature and uses case studies. Data collection techniques using observation, in-depth interviews and documentation. The conclusion of this study is that the credibility of the @edukasiparlemen account is formed due to direct interaction between Instagram followers and the Public Relations Secretariat General of the DPR RI, education delivered on Instagram is the same as offline education. Instagram followers @edukasiparlemen are dominated by high school / vocational students, students and the academic community. Published content about parliamentary education includes Did you know?, Contact Yuk, Sunmori, quizzes, etc. The contents are very clear and interactive so that they get considerable attention from followers.  Keywords: DPR RI, Public Relation, Image, Education, Instagram